العلاقة بين الكفاءة الذاتية ونتائج تعلم اللغة العربية لدى الطلاب بالمدرسة الثانوية الحكومية ٤٣ جاكرتا - Fadilah Indah Octa Azahra; N. Lalah Alawiyah; Iman Matin (Penerbit Minhaj Pustaka, 2025)
ABSTRACT This study aims to examine the relationship between self-efficacy and Arabic language learning outcomes among eleventh-grade students at State Senior High School 43 Jakarta. Self-efficacy refers to an individual's belief in their ability to complete academic tasks, significantly influencing motivation, persistence, and academic achievement. The research employed a quantitative method with a correlational approach. Data were collected through a self-efficacy questionnaire and students’ Arabic language test scores administered by the teacher. The data were analyzed using Pearson correlation and simple regression analysis to measure the strength of the relationship between the two variables. The results revealed a statistically significant positive correlation, with a correlation coefficient of 0.653, indicating that students with higher self-efficacy tend to achieve better results in Arabic language learning. Furthermore, the study found that self-efficacy is influenced by several factors, including previous successful experiences, teacher and peer support, as well as the application of active and interactive teaching strategies in the classroom. Based on these findings, the study concludes that enhancing students’ self-efficacy can be an effective strategy to improve their Arabic language learning outcomes.